Mapping surface deformation in open pit iron mines of Carajas Province (Amazon Region) using an integrated SAR analysis - Paradella, Waldir R.; Ferretti, Alessandro; Mura, Jose C.; Colombo, Davide; Gama, Fabio F.; Tamburini, Andrea; Santos, Athos R.; Novali, Fabrizio; Galo, Mauricio [UNESP]; Camargo, Paulo O. [UNESP]; Silva, Arnaldo Q.; Silva, Guilherme G.; et al. (Elsevier B.V., 2015)
The Carajas mineral province encompasses the world's largest iron reserves with excavation carried out through open pit benching. Mining operations in the area have significant areas of rock mass movements and surface displacements that potentially lead to slope instabilities with risks to personnel, equipment and production. Instabilities can be expected due to deep excavations in rock masses of low geomechanical quality, blasting practices and heavy precipitation. In this paper, ground instabilities are monitored through an integrated SAR analysis based on a data-stack of 33 TerraSAR-X images. This approach was designed to monitor distinct displacement regimes, ranging from small to high deformation rates, and to map surface changes, based on variations of radar reflectivity. Results were compared with field information (total station/prisms, ground based radar, geological and geomechanical maps), and the approach showed to be effective for monitoring ground deformation in the region. Due to its capabilities (synoptic view, high accuracy, dense grid sampling), the complementary use of space-based SAR with field monitoring systems proved to be strategic for operational mining planning and risk assessment in this challenging environment. (C) 2015 The Authors. Published by Elsevier B.V.
Keywords: DInSAR; TerraSAR-X; Mining areas; Geodetic monitoring; Open pit deformation; Amazon region